A Middle Bronze II Cylinder Seal of North Syrian Style from Tel Shimron (Jezreel Valley) - Roßberger, Elisa (Bulletin of ASOR, 2021)
The first excavation season at Tel Shimron brought to light a well-preserved hematite cylinder seal of outstanding artistic quality dating to the Middle Bronze IIA-B. The depicted creatures belong to the Egyptian and Syro-Levantine art spheres, but their rendering and the integration of additional pictorial elements conforms more to the latter. Stylistically, the seal relates to the Northern Levantine coastal region, and in particular to a group characterized by its deep and fluid linear carvings and plastic modeling of animal bodies in motion. Together with an example from Tell el-ʿAjjul, its discovery in the Jezreel Plain marks the southern-most secured findspot for a seal of this style, and offers a welcome opportunity for a renewed discussion on processes of artistic interaction and hybridization in the Middle Bronze Age Levant.